Fragmentation, métropolisation et résilience des formes urbaines à Alger - Aniss M. Mezoued (Cybergeo, 2022)
This article questions the resilience of urban forms in the processes of metropolization of the city of Algiers. Through the morphological analysis of urban fabrics’ fragments located along the tramway, this text questions the capacity of these different forms to adapt to change. The arrival of this new transport infrastructure, presented by the public authorities as a lever for metropolization and reduction of spatial fragmentation, is an opportunity to explore the transformations at work in the fabric and the adaptation of urban forms to the changes that have occurred. It shows that the urban production of public sector actors and large private real estate operators contributes to the processes of metropolization, but in many cases accentuates spatial fragmentation with urban forms that are not very resilient. This text also shows that the ordinary ‘self-constructed’ city, although criticized by the official discourse, seems to adapt better to change. It creates resilient urban forms that go beyond spatial fragmentation, on the one hand, and contribute to the processes of metropolization on the other hand.